Efectos de la estimulación transcraneal por corriente directa en pacientes con fibromialgia - Ruiz Cardenas, Alejandra (2023)
ABSTRACT: Fibromyalgia is a chronic condition of widespread pain, which is associated with symptoms of anxiety, tiredness and sleep problems. Its pathophysiology is still imprecise, it is considered to be related to variations in pain and sensory processes in the brain and spinal cord, mainly in nociception pathways. The research project was developed through the bibliographic review modality, in which relevant scientific documentation was collected on transcranial direct current stimulation (tDCS) in patients with Fibromyalgia with the aim of identifying the effectiveness and benefits of the technique in said pathology. 99 scientific documents were collected, selecting 35, which met the exclusion and inclusion criteria, obtaining scores greater than or equal to 6 on the PEDro scale. The databases from which information on the proposed topic was acquired were: PubMed, Scielo, Elsevier, among others. The various non-invasive brain stimulation techniques achieve great benefit in chronic pain pathologies, including fibromyalgia. Transcranial direct current stimulation (tDCS) is a potential, noninvasive procedure that applies a low intensity current (1 to 2 mA) to the scalp for about 20 minutes. The reviewed articles reveal that by applying tDCS at the level of M1 (primary motor cortex) in patients with fibromyalgia, pain is reduced in the short and medium term and also brings improvement in the pressure pain threshold, catastrophism and the quality of life. Keywords: Transcranial Stimulation, Fibromyalgia, Non-Invasive Brain Stimulation, Motor Cortex.